2010
DOI: 10.1111/j.1752-7325.2009.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

The dental office visit as a potential opportunity for diabetes screening: an analysis using NHANES 2003-2004 data

Abstract: As almost all individuals with periodontitis would have been recommended for diabetes screening, and many at-risk persons with periodontal disease recently visited a dentist, our data suggest that the dental visit provides an important potential venue for this screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
57
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 30 publications
0
57
0
1
Order By: Relevance
“…It was over 20 years ago when Löe suggested that periodontal disease is the 6th complication of diabetes [10]. Since then, much has been written about how OHCPs are uniquely positioned to screen patients for diabetes and prediabetes [11][12][13]. Just as screening dental patients for hypertension became a standard of care 50 years ago, screening for diabetes should become a standard of care and no longer considered optional in routine dental visits.…”
Section: Introductionmentioning
confidence: 99%
“…It was over 20 years ago when Löe suggested that periodontal disease is the 6th complication of diabetes [10]. Since then, much has been written about how OHCPs are uniquely positioned to screen patients for diabetes and prediabetes [11][12][13]. Just as screening dental patients for hypertension became a standard of care 50 years ago, screening for diabetes should become a standard of care and no longer considered optional in routine dental visits.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis is considered to be a complication of diabetes mellitus [6,7] and therefore it has been suggested that dentists could help to screen for diabetes [8][9][10][11]. Periodontitis is a chronic multifactorial inflammatory disease of the tooth supporting structures [10].…”
Section: Introductionmentioning
confidence: 99%
“…23,24 In addition, the high risk for diabetes among individuals with periodontal disease 25-30 has motivated some to suggest the potential of the dental visit as another opportunity for diabetes screening. 31-34 …”
Section: Introductionmentioning
confidence: 99%